Multiyear Measurements of the Aerosol Absorption Coefficient Near the Surface in a Small-Sized Urban Area in Portugal - Nepomuceno Pereira, Sérgio (2014)
Measurements of the aerosol absorption coefficient, between 2007 and 2013, were made at the ground level in Évora, a Portuguese small town located in the southwestern Iberia Peninsula. Such a relatively long time series of absorbing aerosols is unique in Portugal and uncommon elsewhere.The average aerosol absorption coefficientwas close to 9Mm−1 and clear cycles at both daily and seasonal time scales were found. An average increase by a factor of two (from 6 to 12Mm−1) was observed in winter if compared to summer season. The daily variations were similarly shaped for all seasons, with two morning and afternoon peaks, but with magnitudes modulated by the seasonal evolution. That was not the case if Sundays were considered. These variations can be explained in terms of the impact of local particle sources, related mainly to traffic and biomass burning and upward mixing of the aerosol due to variable mixing layer heights, either daily or seasonally. Also, a strong negative correlation between the aerosol absorption coefficient and the wind speed was verified, and an exponential decay function was found to fit very well to the data.The wind direction seems to be not correlated with the aerosol absorption coefficient.